(untitled) (Herald of Journalism, 2016)
The scientific article is devoted to the study of the use of information technologies in armed clashes. Given the history of the concept of « information warfare», examines ways of its development, as well as evidence, concrete examples. Along with this, the basic problem of the use of information technologies in armed clashes. Also, the author investigated the characteristics of armed conflicts of recent years and tried to comprehensively examine the responsibility of the media for publishing news of an armed clash.